2021
DOI: 10.1002/nau.24603
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time daily assessment of work interference on healthcare professionals' restroom use: A pilot study

Abstract: Aims Certain occupations may predispose individuals to develop lower urinary tract symptoms presumably through the adoption of unhealthy toileting behaviors. This study aimed to pilot the feasibility of recording healthcare workers' perceptions of daily, work‐related interference with toilet use using a cellular, text‐based survey tool. Methods A cohort study of adult healthcare professionals completed a baseline questionnaire, a daily survey for fourteen consecutive days regarding their restroom use for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The continuous development of Internet technology has enabled the medical industry to enter the digital age, and Internet technology has also begun to be used in clinical nursing, which has simplified and upgraded the work of medical staff. With the continuous development of the Internet, the medical IoTs have begun to enter the clinical urinary real-time nursing system, which has brought more convenience to the hospital staff [ 5 ]. The hospital's information system can be connected to and transformed with the clinical information system, making the hospital's work process more convenient, improving the overall work efficiency of the hospital, and making the hospital's service satisfaction better [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The continuous development of Internet technology has enabled the medical industry to enter the digital age, and Internet technology has also begun to be used in clinical nursing, which has simplified and upgraded the work of medical staff. With the continuous development of the Internet, the medical IoTs have begun to enter the clinical urinary real-time nursing system, which has brought more convenience to the hospital staff [ 5 ]. The hospital's information system can be connected to and transformed with the clinical information system, making the hospital's work process more convenient, improving the overall work efficiency of the hospital, and making the hospital's service satisfaction better [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that these participants are likely to have fewer risk factors for renal impairment apart from their working hours, it suggests a more pronounced hazardous effect of long working hours on renal health. A previous cohort study among adult HCW indicated that increased work burden correlated with a decreased frequency of voiding daily (30). Moreover, unhealthy behaviors such as inadequate water consumption and delayed voiding are known to contribute to kidney problems (31).…”
Section: Discussionmentioning
confidence: 99%
“…In Xu’s study [ 18 ], nurses often engage in unhealthy toileting behaviors such as delayed urination to adapt to occupational stress. Increased work burden was in turn found to be associated with the number of breaks and limitations to restroom use, which led to increased delayed urination behavior [ 19 ]. Strong evidence for the relationship between sleep, delayed urination, and transition shock is still lacking.…”
Section: Introductionmentioning
confidence: 99%